Performance of an integrated solar absorption cooling system in a sub-tropical region - Darkwa, Jo; Fraser, S. (Oxford University Press, 2012)
Evaluation of an integrated solar absorption cooling system located in a sub-tropical region has been carried out. Analysis of the results revealed an operational efficiency of 61% for the solar collectors at a mean differential temperature forumla of 51°C when compared with the manufacturer's rating of 70% at 60°C. The absorption chiller did, however, perform quite satisfactorily and achieved a coefficient of performance of 0.69 when compared with the manufacturer's rating of 0.7. There is however the need for the hot water supply system to be optimized as well as provision for supplementary heat source in order to maintain the appropriate operating temperature during low solar radiation levels.